Complete response following treatment of plasma cell leukemia with venetoclax and dexamethasone: A case report. (July 2022) - Vo, Kim; Guan, Tiffany; Banerjee, Rahul; Lo, Mimi; Young, Rebecca; Shah, Nina
Introduction: Plasma cell leukemia (PCL) is a rare but aggressive variant of multiple myeloma (MM) with a poor prognosis. Due to the limited number of prospective clinical trials studying PCL, treatment options are often extrapolated from data available for the treatment of MM. Venetoclax has recently demonstrated antimyeloma activity in patients with relapsed/refractory MM carrying the t(11;14) translocation. However, few cases have reported the analogous efficacy of venetoclax in PCL. Case Report: A 64-year-old Caucasian male developed relapsed PCL despite treatment with hyperCD (hyperfractionated cyclophosphamide and dexamethasone) and Dara-KRd (daratumumab, carfilzomib, lenalidomide, dexamethasone). Due to the refractory nature of his disease and the presence of a t(11:14) translocation, the patient was subsequently initiated on venetoclax 400 mg daily and dexamethasone 4 mg once weekly. Management and outcome: The patient achieved a complete response by International Myeloma Working Group criteria three months after initiating venetoclax-dexamethasone, including a repeat bone marrow biopsy that showed no abnormal plasma cells. He successfully underwent consolidation with melphalan-based autologous stem cell transplantation. He remains disease-free 9 months after venetoclax initiation. Discussion: Combination all-oral therapy with venetoclax and dexamethasone can induce deep hematologic responses in patients with relapsed/refractory PCL carrying the t(11;14) translocation.